2010
DOI: 10.1111/j.1742-481x.2010.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating antimicrobial efficacy of new commercially available silver dressings

Abstract: Prevention and treatment of bacterial colonised/infected wounds are critical. Many commercially available silver dressings claim broad-spectrum bactericidal activity over days and are indicated for serious conditions including burns and ulcers. However, there is no peer-reviewed literature available for many newer dressings. This study compared the activity of some of these dressings. Six silver-containing dressings were compared using log reduction, silver release and corrected zone of inhibition assays. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 25 publications
1
47
0
1
Order By: Relevance
“…The low efciency of antibacterial agents, multiple adverse reactions dictate the need of searching for new highly effective remedies. So, researchers often pay attention to herbal substances as sources for biologically active compounds which have a modifying activity against the pathogenic and persistent potential of microbes [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The low efciency of antibacterial agents, multiple adverse reactions dictate the need of searching for new highly effective remedies. So, researchers often pay attention to herbal substances as sources for biologically active compounds which have a modifying activity against the pathogenic and persistent potential of microbes [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are Acticoat (Smith & Nephew), Actisorb Silver 220 (Johnson & Johnson), Aquacel -Ag (Convatec), Arglaes (Medline, Mundelein), Contreet -H (Coloplast, Marietta), SilvaSorb (Medline) and Silverlon® (Argentum LLC). The comparison of the silver dressings is usually based on the bacteriology (Cavanagh et al, 2010). Thus, differences are noticed in the field of inhibition, with Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) as a result of the antimicrobial activity of the agent.…”
mentioning
confidence: 99%
“…Hydrofibre and alginate dressings are very rarely used for paediatric patients in Australasia. Multiple research studies [10][11][12][13][14][15] have shown silver to be effective against a variety of gram positive and negative bacteria. While it is well known that silver can be cytotoxic to healthy keratinocytes, prevention of infection, in particular toxic shock syndrome, even in small burns, is prioritized over promoting wound re-epithelialization for paediatric patients in Australia and New Zealand.…”
Section: Treatmentmentioning
confidence: 99%
“…Acticoat TM has been found in a number of in vitro trials to be effective against a broad spectrum of Gram positive and Gram negative bacteria [10][11][12][13][14][15]. Furthermore, Acticoat™ when used to treat patients with burn injuries was found to be significantly associated with a lower rate of adverse events (colonizations or infections) than those participants treated with the SSD or other non-silver dressings and applications [11,12].…”
Section: Antimicrobial Properties Of Silver Dressingsmentioning
confidence: 99%
See 1 more Smart Citation